Eficiencia de la gestión de recursos hídricos en juntas administradoras de agua potable del cantón Chone - Montesdeoca Palma, Silvia Maholy (2025)
Access to safe drinking water is a fundamental right intrinsically linked to well-being, particularly in rural contexts where its management is entrusted to community-based organizations. This research aimed to assess the efficiency of public water resource management in the potable water administrative boards of the Chone canton during the first half of 2024, with the objective of identifying improvement opportunities that enhance sustainability. A non-experimental, cross-sectional methodology with a mixed, descriptive, and exploratory approach was employed. Data collection involved interviews with local authorities and users, as well as an analysis of technical documentation and the operational conditions of the boards. The initial diagnosis revealed significant deficiencies in water quality, service continuity, and community participation—factors that adversely affect both the operational performance and users' perception of the service. Findings indicate technical, administrative, and financial constraints that hinder the boards' ability to ensure a reliable and efficient service. In response, a management indicator system was developed, focusing on measuring operational efficiency, user satisfaction, and transparency. This system was complemented by an improvement plan that includes preventive maintenance, personnel training, and institutional strengthening. It is concluded that the systematic implementation of these indicators constitutes a key decision-making tool, contributing to more efficient, equitable, and sustainable management of drinking water services in the communities of Chone canton.